Studies of the lifetime of cyclically loaded steel-concrete composite bridges - Hanswille, Gerhard; Porsch, Markus; Ustundag, Cenk (Wiley, 2010)
In current German and international standards for composite structures of steel and concrete, the determination of the ultimate load capacity and the fatigue life of headed shear studs is carried out with separate and independent verifications at the ultimate, serviceability and fatigue limit states. The fatigue resistance is verified in a similar way to steel structures, based on a nominal stresses concept and linear damage accumulation according to Palmgren-Miner. The effect of pre-damage due to fatigue loading at both the ultimate and serviceability limit states is not considered. Because cyclic loading of headed shear studs leads to a decrease in the static strength of stud connectors, the assumptions for independent limit states are not given and the reliability index of steel-concrete composite structures subjected to fatigue loading may fall below the target values in codes. This paper deals with the results of a comprehensive programme of experimental work with more than 90 standard EC4 push-out test specimens and two full-scale beam tests which consider the crack propagation through the stud foot and the local damage to the concrete surrounding the studs as relevant consequences of highcycle loading. Based on the results of the push-out tests, new design methods were developed to predict the fatigue life and the residual strength of headed shear studs after high-cycle loading. Considering the interaction between the local damage and the behaviour of the global structure, these research results were taken as the basis for simulating the cyclic behaviour of composite beams by means of a damage accumulation method.